Priorities and challenges in social and healthcare policies for older people living in the Mediterranean basin: A Delphi panel study - Ana María Porcel-Gálvez; Regina Allande-Cussó; Elena Fernández-García; Salma Essawi; Mohamed Salama; Saly Sami Saad; Rafael-Jesús Fernández-Castillo; Marta Lima Serrano (BMC Geriatrics, 2024)
Abstract Background Recently, the countries in the Mediterranean basin (which share cultural ties) have been showing a common trend of declining social support for the elderly, with deficiencies in social care models for this demographic. Thus, this Delphi panel study analyzed the gaps in social and integrated care among the participating countries in a European research project. Methods This three-round Delphi panel study focused on the European countries of Greece and Spain and the non-European countries of Egypt, Lebanon, and Tunisia. In this project, experts were identified according to their level of expertise in the subject matter, their gender, and their membership in different social groups. Subsequently, they were asked to identify the current situation of social care, set future goals, and locate the gaps regarding the social and healthcare models for older people in the participating countries. The median score (Mdn) and interquartile range (IQR) were calculated to assess the degree of consensus on the different priorities. Results Among the participating countries, there was a lack of state agreements to maintain social care models, a lack of coordination between public and private institutions to provide social care services, territorial inequalities in terms of access and coverage of rights, and job insecurity for professionals. The desired situation was to integrate social and healthcare services with a person-centered social care model, thus promoting autonomy and empowering users and families in participation and decision-making. Conclusions This Delphi study reveals significant disparities in social and healthcare policies for older adults across Mediterranean countries, highlighting shared challenges and specific national needs. European nations like Greece and Spain face fragmented systems, while non-European countries such as Lebanon, Egypt, and Tunisia lack specialized geriatric services and social security. All countries urgently need better professional training, social and economic empowerment of older adults, and integrated national strategies. These findings offer key insights for policymakers to develop equitable, sustainable solutions for aging populations.